Impact of target area selection in 125 Iodine seed brachytherapy on locoregional recurrence in patients with non‐small cell lung cancer. Issue 3 (20th February 2017) - Yan, Wei‐Liang; Lv, Jin‐Shuang; Guan, Zhi‐Yu; Wang, Li‐Yang; Yang, Jing‐Kui; Liang, Ji‐Xiang
Abstract : Background: Computed tomography (CT)‐guided percutaneous implantation of 125 Iodine radioactive seeds requires the precise arrangement of seeds by tumor shape. We tested whether selecting target areas, including subclinical areas around tumors, can influence locoregional recurrence in patients with non‐small cell lung cancer (NSCLC). Method: We divided 82 patients with NSCLC into two groups. Target areas in group 1 ( n  = 40) were defined along tumor margins based on lung‐window CT. Target areas in group 2 ( n  = 42) were extended by 0.5 cm in all dimensions outside tumor margins. Preoperative plans for both groups were based on a treatment plan system, which guided 125 I seed implantation. Six months later, patients underwent chest CT to evaluate treatment efficacy (per Response Evaluation Criteria in Solid Tumors version 1). We compared locoregional recurrences between the groups after a year of follow‐up. We then used the treatment plan system to extend target areas for group 1 patients by 0.5 cm (defined as group 3 data) and compared these hypothetical group 3 planned seeds with the actual seed numbers used in group 1 patients. Results: All patients successfully underwent implantation; none died during the follow‐up period. Recurrence was significantly lower in group 2 than in group 1 ( P  < 0.05). Group 1 patients and group 3 data significantly differed in seed numbers ( P  < 0.01). Conclusion: Our results imply that extending the implantation area for 125 I seeds can decrease recurrence risk by eradicating cancerous lymph‐duct blockades within the extended areas.